Komunikasi, Informasi dan Edukasi Pencegahan Covid-19 di Panti Asuhan Kecamatan Panyileukan Bandung - Winasih Rachmawati; Ani Anggriani; Emma Emawati; Garnadi Jafar; Irisanna Tambunan (ABDI: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2022)
The Covid-19 pandemic in Indonesia is increasing until the end of 2020, this is due to a lack of public understanding to overcome the spread transmission of the Covid-19 virus, including as wearing masks, keeping a safe distance, and maintaining good hand hygiene. Awareness of this behavior is very low in orphanages so that it may accelerate the transmission of the Covid-19 virus. Therefore, it is necessary to provide Communication, Information and Education (CIE) related to preventing the transmission of the Covid-19 virus to residents of orphanages in the area around Panyileukan District, Bandung City, West Java. This activity was carried out in two orphanages located in the area for two months. The activity began with the creation of information media, knowledge surveys, cadre training, Covid prevention education, making hand sanitizers and disinfectants, and final evaluation. The result showed that there is a relationship between knowledge and actions after being given CIE methods in orphanages to avoid the transmission Covid-19.